Analysis of Student Satisfaction in the MBKM Internship Program Based on Internship Experience: A Study of Students at Jenderal Soedirman University - Kurniasih, Retno; Pradisti, Larisa (Valid: Jurnal Ilmiah, 2025)
This research aims to analyze the level of student satisfaction preferences towards internships. This research focuses mainly on Jenderal Soedirman University students. The sample selected in this research had criteria in the form of students at Jenderal Soedirman University who had carried out an internship program, either an Independent Learning Campus (MBKM) internship or an independent internship. Researchers used several methods in this research, such as the Tolerance Value and Variance Inflation Factor (VIF) test, the Heteroscedasticity Test using the Park test method, the Normality Test using the non-parametric Kolmogorov-Smirnov (k-s) statistical test method, and the Autocorrelation Test by testing the Durbin-Watson value. The research results show that 1) Positive Internship does not have a positive and significant effect on Internship Satisfaction, 2) Positive Work Environment has a positive and significant effect on Internship Satisfaction, 3) Improved Job Prospect does not have a positive and significant effect on Internship Satisfaction, 4) News Skills has a positive and significant effect on Internship Satisfaction, 5) Comfort With Work Environment does not have a positive and significant effect on Internship Satisfaction, 6) Communication does not have a positive and significant effect on Internship Satisfaction